Determination of maximum turbulent energy dissipation rate generated by a rushton impeller through large eddy simulation. Issue 10 (23rd August 2013) - Soos, Miroslav; Kaufmann, René; Winteler, Raphael; Kroupa, Martin; Lüthi, Beat
<x xml:space="preserve">Abstract</x> Large eddy simulation (LES) of a stirred tank equipped with a Rushton impeller and four cylindrical baffles was used to characterize the flow pattern and to assess the maximum turbulent kinetic energy dissipation rate εmax. While the shorter baffle‐impeller distance significantly affects the radial velocity profile and the trailing vortices expansion, the flow field in the impeller vicinity is comparable to that of a standard setup with rectangular baffles connected to the wall. The phase‐resolved profile of εmax indicates its very strong variation from 10 · N3D2 to 130 ± 13 · N3D2. When using peak values of the corresponding hydrodynamic stress <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3h87rqpp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />τmax⁡(=μρεmax⁡)</alternatives>, the maximum stable aggregate size measured in the same stirred tank closely correlates with breakage data obtained under laminar conditions using the same initial aggregates. This indicates that the same mechanism was involved in the aggregate breakup under both conditions, allowing us to predict aggregates breakup under various conditions. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3642–3658, 2013